Immune Checkpoint Inhibitors +/− Chemotherapy for Patients With NSCLC and Brain Metastases: A Systematic Review and Network Meta‐Analysis - Lauren Julia Brown; Nicholas Yeo; Harriet Gee; Benjamin Y. Kong; Eric Hau; Inês Pires daSilva; Adnan Nagrial (Thoracic Cancer)
ABSTRACT Background Multiple studies have demonstrated the intracranial efficacy of immune checkpoint inhibitors (ICI) +/− chemotherapy. The efficacy of chemoimmunotherapy compared to ICI alone in patients with metastatic NSCLC and brain metastases (BM) remains unknown. Methods A systematic review and network meta‐analysis were performed to evaluate ICI efficacy and the influence of additional chemotherapy on survival outcomes in treatment‐naïve metastatic NSCLC with BM. Randomized phase II/III studies with at least one treatment arm with an ICI were eligible. Overall survival (OS) and progression‐free survival (PFS) in patients with and without BM were assessed. Results Ten studies were included, totaling 6560 patients, 770 with BM. Pairwise meta‐analysis revealed that patients with BM treated with ICI +/− chemotherapy had improved PFS (hazard ratio [HR] 0.49; 95% CI 0.40–0.60) and OS (HR 0.55; 95% CI 0.44–0.68) versus chemotherapy alone. Patients without BM treated with ICI +/− chemotherapy also had improved PFS and OS compared to chemotherapy alone. In the network meta‐analysis of patients with BM, chemoimmunotherapy demonstrated improved PFS compared to ICI alone (HR 0.64; 95% CI 0.43–0.96; p = 0.03). No significant difference was observed in OS. In the population of patients without BM, no significant differences in PFS or OS were observed between chemoimmunotherapy versus ICI alone. Conclusion This meta‐analysis confirms that ICIs with or without chemotherapy are superior to chemotherapy alone for the first‐line management of metastatic NSCLC with and without BM. This network meta‐analysis suggests combination chemoimmunotherapy offers PFS benefit over ICI monotherapy in BM patients, warranting direct comparisons in clinical trials. Trial Registration: PROSPERO: CRD42024501345